Fundamentals of nursing - Potter, Patricia Ann.; Perry, Anne Griffin; Hall, Amy (Amy M.); Stockert, Patricia A. (St. Louis, Mo.: Mosby Elsevier, 2013)
This 8th edition includes accurate, cutting-edge content, active learning strategies, and the latest evidence-based research to help you excel in your classes and prepare for success in today's competitive nursing field. An expert author team led by Patricia Potter and Anne Griffin Perry provides a trusted, comprehensive resource, thoroughly reviewed by nursing experts and peers to ensure the most accurate content. With practical, fully integrated study support, this edition makes it easier than ever to build the understanding and clinical reasoning essential to providing excellent patient care. Building competency boxes help you apply QSEN (Quality & Safety Education for Nurses) competencies to realistic clinical situations. Expanded Evidence-based practice boxes highlight the importance of current clinical research in daily practice. Case studies in all clinical chapters allow you to practice using care plans and concept maps to perform clinical application exercises. Clinical application questions test your understanding of clinical practices. Skill guidelines for blood glucose monitoring help you ensure accurate readings when performing this common skill. Content on violence, genetics/genomics, compassion fatigue, bullying, and the accreditation process addresses current concerns in nursing practice. More than 725 review questions test your retention of key chapter concepts. Three comprehensive fundamentals practice exams and a calculations tutorial on the companion. More than 100 new photos clarify procedures and familiarize you with the latest clinical equipment. Glossary provides quick, convenient access to definitions for all key terms.--
Nursing today -- The health care delivery system -- Community-based nursing practice -- Theoretical foundations of nursing practice -- Evidence-based practice -- Health and wellness -- Caring in nursing practice -- Caring for the cancer survivor -- Culture and ethnicity -- Caring for families -- Developmental theories -- Conception through adolescence -- Young and middle adults -- Older adults -- Critical thinking in nursing practice -- Nursing assessment -- Nursing diagnosis -- Planning nursing care -- Implementing nursing care -- Evaluation -- Managing patient care -- Ethics and values -- Legal implications in nursing practice -- Communication -- Patient education -- Documentation and informatics -- Patient safety -- Infection prevention and control -- Vital signs -- Health assessment and physical examination -- Medication administration -- Complementary and alternative therapies -- Self-concept -- Sexuality -- Spiritual health -- The experience of loss, death, and grief -- Stress and coping -- Activity and exercise -- Hygiene -- Oxygenation -- Fluid, electrolyte, and acid-base balance -- Sleep -- Pain management -- Nutrition -- Urinary elimination -- Bowel elimination -- Mobility and immobility -- Skin integrity and wound care -- Sensory alterations -- Care of surgical patients.
Previous edition: 2009 had main entry under Potter, Patricia Ann.
Includes bibliographical references and index.
Keywords: Nursing -- Textbooks; Nursing -- Practice -- Textbooks; Nursing; Nurse and patient; Nursing